A Review of a Groundwater Quality Study based on the theoretical and literature evidence (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The most important and significant source of potable water in the world is groundwater. In the state of Jharkhand, groundwater is utilised for a variety of reasons, including irrigation, mining, residential usage, and even drinking water. Because the groundwater in many areas of Jharkhand is contaminated with dangerous chemicals such as fluoride, arsenic, heavy metals, and iron, amongst others, certain populations in Jharkhand are forced to endure water shortages due to a lack of access to clean drinking water, while other populations only have limited access to this resource. This study looks at the present situation of groundwater in Jharkhand, as well as the pollution of several water quality metrics based on the chemistry of key ions. Water temperature, pH, electrical conductivity, total dissolved solid, total hardness, calcium, magnesium, iron, sodium, potassium, chloride, fluoride, arsenic, carbonate, bicarbonate, phosphate, nitrate, and sulphate are the water quality characteristics that are covered in this research.